Teachers tackle thinking - Clasen, Rae; Geier, Dick (United States : University Winconsin ; distributed by Great Plains National, 1988)
Contains 10 volumes of teachers tackle thinking. Developing of effective thunking strategy to be effective thinkers among students
vol. 1. Developing effective thinkers - vol. 2. Classroom climate - vol. 3. Questioning - vol. 4. Deductive reasoning - vol. 5. Inductive reasoning - vol. 6. Problem solving - vol. 8. Enhancing thinking with computers - vol. 9. Enhancing thinking in language arts - vol. 10. Enhancing thinking in mathematics - vol. 12. Enhancing thinking in science
Copy available in DVD format
Editor, Clark Thompson
Keywords: Thought and thinking; Teaching